Effect of Protein and Amino Acid Levels on Bone Formation in Diets Varying in Calcium Content - Coto, C.; Wang, Z.; Cerrate, S.; Perazzo, F.; Abdel-Maksoud, A.; Yan, F.; Waldroup, P.W. (International Journal of Poultry Science, 2009)
The effect of different dietary levels of amino acids, calcium and phosphorus as influenced by phytase supplementation was evaluated in broiler chickens. The experimental design consisted of a 3 x 4 x 2 factorial arrangement with three levels of digestible lysine (1.10, 1.30 and 1.50%), four levels of calcium (0.50, 0.70, 0.90 and 1.1%) and diets containing 0.35% AP with and without phytase for a total of 24 treatments. Remaining amino acids levels were adjusted with respect to the digestible lysine level using the ideal ratios suggested by Rostagno et al. (2005). Each experimental diet was fed to six replicates pens of five male chickens during 21 days. Body weight, FCR, feed intake, bone development (TD), bone mineralization (toe ash), and phosphorus excretion as Total Phosphorus in excreta (TP), Water Soluble Phosphorus in excreta (WSP) and the WSP/TP ratio were evaluated. Birds fed lysine levels higher than 1.1% expressed better body weight in a non-linear trend. Feed intake was decreased by increasing the lysine level while feed conversion improved as lysine level increased. Increasing levels of Ca decreased feed intake, the 1.1% Ca level was detrimental for body weight. Phytase supplementation was effective to alleviate widened-suboptimal Ca:P ratios in terms of feed intake and body weight. The 1.5 % digestible lysine level improved toe ash; however, high levels of lysine were also related to a higher incidence of TD. Ca levels equal or greater than the NRC (1994) recommendation were adequate for optimum bone mineralization. Increasing levels of Ca reduced the incidence and severity of TD. Moreover, Ca levels greater than those suggested by NRC (1994) were adequate to assimilate higher lysine levels without compromising bone development. The higher lysine levels fed reduced TP in excreta but increased the WSP/TP ratio. The supplementation of phytase increased WSP and the WSP/TP ratio. Increasing levels of Ca reduced WSP and the WSP/TP ratio in excreta. Furthermore, high levels of Ca were also effective to overcome the increased WSP and WSP/TP ratio caused by the supplementation of phytase.